Isolation of Symbiotic Bacteria with Red Algae from Tongkaina Waters, North Sulawesi - Elvy Like Ginting; Liviani Rangian; Letha L. Wantania; Stenly Wullur (Sam Ratulangi University, 2019)
This study aims to isolate symbiotic bacteria with red algae from the waters of Tongkaina, North Sulawesi. The red algae taken were red algae that are similar to the genus Portieria and Gracilaria. Bacteria were cultured and isolated using Nutrient Agar (NA) + sea water. Before bacteria from red algae samples were cultured, each sample of red algae was crushed, homogenized and diluted. The results of this study, 5 bacterial isolates were successfully isolated from red algae similar to Portieria sp. and 5 bacterial isolates from red algae similar to Gracilaria sp. Each bacterial isolate has different morphological characteristics such as shape, colour, elevation, and edges. Of the 10 bacterial isolates, 3 bacterial cells are gram-positive cocci (round), and 7 of them are gram-negative bacilli (rod).Keywords: Red algae, bacteria, isolation, symbionts ABSTRAKTujuan dari penelitian ini adalah untuk mengisolasi bakteri simbion dengan alga merah dari perairan Tongkaina, Sulawesi Utara. Alga merah yang diambil adalah alga merah yang mirip dengan genus Portieria dan Gracilaria. Bakteri ditumbuhkan dan diisolasi menggunakan media Nutrien Agar (NA) + air laut. Sebelum bakteri dari sampel alga merah ditumbuhkan, masing-masing sampel alga merah digerus, dihomogeniasi dan diencerkan. Hasil penelitian ini, 5 isolat bakteri berhasil diisolasi dari alga merah mirip Portieria sp. dan 5 isolat bakteri dari alga merah mirip Gracilaria sp. Masing-masing isolat bakteri memiliki karakteristik morfologi yang berbeda seperti bentuk, warna, elevasi, dan tepian. Dari 10 isolat bakteri tersebut, 3 sel bakteri bersifat gram positif dengan bentuk bulat, dan 7 diantaranya bersifat gram negatif dengan bentuk batang.Kata kunci: Alga merah, bakteri, isolasi, simbion